Characterization of In Vitro-Generated and Clinical Optochin-Resistant Strains of Streptococcus pneumoniae Isolated from Argentina - Cortes, Paulo R. (2008)
Fil: Cortes, Paulo R. Universidad Nacional de Córdoba. Departamento de Bioquímica Clínica; Argentina.